Gamification for future workforce studies: cyber-security and efficiency - Adeseye, Aisvarya (My University, 2023)
In this era, organisations' workforce dynamics are ever-changing, triggering the need to conduct frequent workforce studies. Performing workforce studies allows the management to measure employee engagement, well-being, knowledge, diversity and inclusion, discrimination, racism, employee retention and satisfaction. However, organisations face several challenges by utilising traditional workforce studies, such as low response rates, not being aware of the appropriate study timeframe, and requiring significant resource allocation. Gamification is the application of game elements to motivate individuals to achieve specific goals. Currently, the application of gamification is increasing across various industries, such as education, healthcare, and recruitment. Therefore, this research study evaluates the efficiency of gamification strategies for workforce studies within an organisation. Additionally, it explores the cyber security and privacy challenges inherent in implementing gamified platforms within an organisation. This study employs an interview approach to gather qualitative data systematically. This study encompasses a participant pool that comprises 82 professionals representing 5 major sectors such as non-governmental organisations (NGOs), corporate entities, academic institutions, government bodies and healthcare providers. The qualitative data were analysed using thematic analysis, and the comprehensive examination identified 21 distinct themes. The participants unanimously stated that the gamified platform for workforce studies will not replace the traditional approaches; rather, it will be supplementary and supportive of the existing approaches. Moreover, participants also mentioned that the employees should be allowed to engage with the gamified platform weekly. This regular participation could ensure continuous monitoring that could indicate to the management when the optimal time to conduct the traditional workforce studies is. Moreover, participants pointed out that there is a need for a balance between the security measures and efficiency of the gamified platform to ensure successful implementation. This research also provides four recommendation stages (designing and implementation, roll-out, maintenance, and success rate determinant matrix) for any organisation that plans to implement a gamified platform for future workforce studies.
Keywords: Gamification, Workforce studies, Cyber-security, Privacy, Efficiency, Gamified Platform